Environmental public health risks in European metropolitan areas within the EURO-HEALTHY project - Mitsakou, Christina; Dimitroulopoulou, Sani; Heaviside, Clare; Katsouyanni, Klea; Samoli, Evangelia; Rodopoulou, Sophia; Costa, Claudia; Almendra, Ricardo; Santana, Paula; Dell'Olmo, Marc Marí; Borrell, Carme; Corman, Diana; et al. (The Science of the total environment, 2019)
Urban areas in Europe are facing a range of environmental public health challenges, such as air pollution, traffic noise and road injuries. The identification and quantification of the public health risks associated with exposure to environmental conditions is important for prioritising policies and interventions that aim to diminish the risks and improve the health of the population. With this purpose in mind, the EURO-HEALTHY project used a consistent approach to assess the impact of key environmental risk factors and urban environmental determinants on public health in European metropolitan areas. A number of environmental public health indicators, which are closely tied to the physical and built environment, were identified through stakeholder consultation; data were collected from six European metropolitan areas (Athens, Barcelona, Lisbon, London, Stockholm and Turin) covering the period 2000-2014, and a health impact assessment framework enabled the quantification of health effects (attributable deaths) associated with these indicators. The key environmental public health indicators were related to air pollution and certain urban environmental conditions (urban green spaces, road safety). The air pollution was generally the highest environmental public health risk; the associated number of deaths in Athens, Barcelona and London ranged between 800 and 2300 attributable deaths per year. The number of victims of road traffic accidents and the associated deaths were lowest in the most recent year compared with previous years. We also examined the positive impacts on health associated with urban green spaces by calculating reduced mortality impacts for populations residing in areas with greater green space coverage; results in Athens showed reductions of all-cause mortality of 26 per 100,000 inhabitants for populations with benefits of local greenspace. Based on our analysis, we discuss recommendations of potential interventions that could be implemented to reduce the environmental public health risks in the European metropolitan areas covered by this study.
Keywords: Air Pollution; Cities; Europe; Public Health; Evropa; znečištění ovzduší; dopravní nehody; environmentální zdraví; Health Impact Assessment; Noise; Green spaces; Accidents, Traffic; hodnocení vlivů na zdraví; Humans; Environmental public health risks; hluk; velkoměsta; Environmental Health; Road traffic noise; Health impact assessment; veřejné zdravotnictví; Air pollution; lidé; Attributable mortality